A competing endogenous RNA network reveals key lncRNAs associated with sepsis. Issue 1 (25th November 2020) - Guo, Xuan; Qin, Yanjun; Wang, Lili; Dong, Shimin; Yan, Yan; Bian, Xiaohua; Zhao, Caiyan
Abstract: Background: This study set out to determine key lncRNAs correlated with sepsis via constructing competing endogenous RNA (ceRNA) network. Methods: Three septic patients and three healthy controls were recruited to obtain lncRNA profiles in this current study. Combined with the mRNA profiles by RNA‐sequencing, an integrated analysis of mRNA expression profiles downloaded from GEO was performed to obtain the differentially expressed mRNAs (DEmRNAs). Based on differentially expressed lncRNAs (DElncRNAs) and DEmRNAs acquired in this present study and differentially expressed miRNAs (DEmiRNAs) acquired in previous study, a ceRNA network was constructed. Furthermore, LINC00963 was validated in THP‐1 cells by performing loss of function assays. Results: In this analysis, a total of 290 DEmRNAs and 46 DElncRNAs were detected in sepsis. Parkinson's disease, Oxidative phosphorylation and Cardiac muscle contraction were significantly enriched KEGG pathways in sepsis. XPO1, CUL4A, and NEDD8 were three hub proteins of sepsis‐specific PPI network. A ceRNA network, which contained 16 DElncRNA‐DEmiRNA pairs and 82 DEmiRNA‐DEmRNA pairs, involving 5 lncRNAs, 10 miRNAs, and 60 mRNAs, was obtained. The function experiments indicated that knockdown of LINC00963 could promote cell proliferation, reduce cytokine expression, and suppress inflammasome activation and phagocytosis in LPS‐induced THP‐1 cells. Conclusion: This study determined key lncRNAs involved in sepsis, which may contribute to the development for novel treatment strategy of sepsis. Abstract :